INVENTORY AND STUDY PHARMACOLOGICAL POTENTIAL OF PLANTS IN THE PAJANGAN HAMLET, WEDOMARTANI, NGEMPLAK, SLEMAN, YOGYAKARTA - Utami, Zidni Meirizka; Rahayu, Fadiah Sri; Yuvita, Arneta; Wardani, Ester Dewanti Yovita; Artik, Arba' Ramadhani; Nuriliani, Ardaning; Sudarsi, Nurini Aru (Jurnal Pendidikan Matematika dan IPA, 2024)
This research aims to inventory and study pharmacological potention of plants in Pajangan Hamlet, Wedomartani, Ngemplak, Sleman, Yogyakarta as medicinal plants and live stalls. The research was conducted from June to October 2023 using observational methods. Plants were identified with PlantNet software and reference againts the Flora of Java book. In addition, the study of the utilization of these plants was carried out by literature study and distributing questionnaires to the residents. The results found 104 plant species with 19 different families can be identified in Pajangan Hamlet. The plants are categorized as herbs, ornamental plants/flowers, fruits, vegetables, and wild plants. These findings highlight the richness of biodiversity in Pajangan Hamlet with significant potentital for improving health and economic livelihoods through the use of local plant species in traditional practices and diets. Based on the result, it can be concluded that Pajangan Hamlet has a variety of plants that are widely used in traditional medicine and food, thereby underscoring the importance of local biodiversity in improving health and well-being.